Referential Processes as Situated Cognition: Pronominal Expressions and the Social Co-Ordination of Talk - Pekarek Doehler, Simona (Antwerp: International Pragmatics Association, 2001)
It has become widely accepted that the functioning of anaphora in discourse is not directly rooted in the text itself but pertains to the mental representations of the speaker and the addressee. The speaker's selection of the linguistic means for expressing reference is understood as essentially grounded in his or her assessment of the recoverability or mental accessibility of the referent to the addressee. According to this principle, most prominently expounded in the work of Ariel (1990), Chafe (1994) and Givón (1979, 1995), speakers tend to use pronouns for highly accessible entities and fuller nominal expressions for less accessible ones. While generally subscribing to the representational model of reference, I would like to suggest that the way speakers code discourse objects cannot be limited to a pure referential functionality. In the present paper, I will sketch the possibility of an alternative view, focusing on the relation between linguistic resources and the social co-ordination of discourse activities. This view is based on three fundamental assumptions: 1. discourse objects are not preestablished entities influencing the way speakers talk or the linguistic resources they select to do so, but are themselves emerging from talk as a social activity; 2. referential processes are crucially involved in the social-interactional organization of this activity and cannot be reduced to the transmission or structuring of informational content; 3. the cognitive correlates of these processes, such as the accessibility or identifiability of referents, are themselves locally contingent socially co-ordinated processes. In what follows, an analysis of face-to-face interactions in French will serve to identify some of the socio-interactional facts that motivate such a view. Uses of informationally minimal referential codings (i.e. pronominal expressions) for long distance anaphora will be examined which present a challenge for current theories of reference. Combining insights from the representational model and an interaction-oriented line of research on reference (Fox 1987, Ford & Fox 1996, Goodwin 1995, Mondada 1995, Sacks 1992), my aim is to show that anaphoric processes rely not merely on shared knowledge about referents, but also - and in some cases essentially - on shared assumptions about the dominant organizational principles of a segment of talk (cf. Pekarek 1999, Pekarek Doehler 2000b). I will argue that these processes are crucially linked to the way talk is co-ordinated as a social-interactional undertaking and that choices of the linguistic means for expressing reference are both motivated by and contributing to organizing the structure of activities deployed in talk. In the final section of this paper, some implications for an understanding of referential processes as situated, reciprocally configured socio-cognitive activities will be sketched.